Mesoporous Y2Sn2O7 pyrochlore with exposed (111) facets: an active and stable catalyst for CO oxidation. Issue 75 (28th July 2016) - Peng, Honggen; Xu, Juan; Tian, Jinshu; Liu, Yang; He, Yunping; Tan, Jin; Xu, Xianglan; Liu, Wenming; Zhang, Ning; Wang, Xiang
Abstract : Mesoporous Y2 Sn2 O7 pyrochlore with exposed (111) facets was successfully synthesized via a simple hydrothermal method and showed superior catalytic performance for CO oxidation. Abstract : Pyrochlore with an A2 B2 O7 crystal structure is a perfect mixed oxide for catalytic application for its high thermal stability. In the present manuscript, mesoporous Y2 Sn2 O7 pyrochlore with exposed (111) facets was successfully synthesized via a simple hydrothermal method and used for CO oxidation. In comparison with Y2 Sn2 O7 prepared by a co-precipitation method (Y2 Sn2 O7 -CP), Y2 Sn2 O7 prepared by a hydrothermal method (Y2 Sn2 O7 -HT) showed superior catalytic performance for CO oxidation. Even after calcination at 800 °C for 4 h (Y2 Sn2 O7 -HT-800), its catalytic performance was still better than that of Y2 Sn2 O7 -CP. Y2 Sn2 O7 -HT is also a good support for Pd nanoparticles. Pd/Y2 Sn2 O7 -HT demonstrates the best performance for CO oxidation among all the catalysts. All the samples were characterized by XRD, SEM, TEM, HAADF-STEM Mapping, N2 adsorption/desorption, H2 -TPR, CO-TPD and Raman spectra to reveal their physicochemical properties. Compared with Y2 Sn2 O7 -CP, Y2 Sn2 O7 -HT has more exposed (111) facets, possesses a higher amount of active surface oxygen species and had high mesoporous surface areas, which should be the reasons accounting for the superior CO oxidation performance of Y2 Sn2 O7 -HT and Pd/Y2 Sn2 O7 -HT. Pd/Y2 Sn2 O7 -HT also shows superior water-tolerance. In wet feed, its catalytic activity was even better than that in dry feed. Therefore, Pd/Y2 Sn2 O7 -HT may be a potential catalyst for practical vehicle emission control.